Identification and properties of the largest subunit of the DNA-dependent RNA polymerase of fish lymphocystis disease virus: dramatic difference in the domain organization in the family Iridoviridae - Müller, Martin; Schnitzler, Paul; Koonin, Eugene V.; Darai, Gholamreza (Journal of general virology, 1995)
Cytoplasmic DNA viruses encode a DNA-dependent RNA polymerase (DdRP) that is essential for transcription of viral genes. The amino acid sequences of the known largest subunits of DdRPs from different species contain highly conserved regions. Oligonucleotide primers, deduced from two conserved domains (RQP[T/S]LH and NADFDGDE) were used for detecting the corresponding gene of fish lymphocystis disease virus (FLCDV), a member of the family Iridoviridae, which replicates in the cytoplasm of infected cells of flatfish. The gene coding for the largest subunit of the DdRP was identified using a PCR-derived probe. The screening of the complete EcoRI gene library of the viral genome led to the identification of the gene locus of the largest subunit of the DdRP within the EcoRI DNA fragment B (12.4 kbp, 0.034 to 0.165 map units). The nucleotide sequence of a part (8334 bp) of the EcoRI DNA fragment B was determined and a large ORF on the lower strand (ATG = 5787; TAA = 2190) was detected which encodes a protein of 1199 amino acids. Comparison of the amino acid sequences of the largest subunits of the DdRP (RPO1) of FLCDV and Chilo iridescent virus (CIV) revealed a dramatic difference in their domain organization. Unlike the 1051 aa RPO1 of CIV, which lacks the C-terminal domain conserved in eukaryotic, eubacterial and other viral RNA polymerases, the 1199 aa RPO1 of FLCDV is fully collinear with its cellular and viral homologues. Despite this difference, comparative analysis of the amino acid sequences of viral and cellular RNA polymerases suggests a common origin for the largest RNA polymerase subunits of FLCDV and CIV.